2018
DOI: 10.1039/c7ra08901e
|View full text |Cite
|
Sign up to set email alerts
|

Is soft independent modeling of class analogies a reasonable choice for supervised pattern recognition?

Abstract: A thorough survey of classification data sets and a rigorous comparison of classification methods show the unambiguous superiority of other techniques over soft independent modeling of class analogies (SIMCA – one class modeling) for classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…The fact that LDA was developed by statisticians, whereas SIMCA was developed by chemists (chemometricians) might contribute to the characteristic differences between their theoretical backgrounds. For example, SIMCA does not require any distributional assumptions, whereas LDA assumes normal distribution and equal variances for each class [37]. In addition, Nikita et al observed that QDA does not give better results than LDA and does not offer an alternative to LDA [38].…”
Section: Chemometrics For Olive Oil Classification According To Its Qmentioning
confidence: 99%
“…The fact that LDA was developed by statisticians, whereas SIMCA was developed by chemists (chemometricians) might contribute to the characteristic differences between their theoretical backgrounds. For example, SIMCA does not require any distributional assumptions, whereas LDA assumes normal distribution and equal variances for each class [37]. In addition, Nikita et al observed that QDA does not give better results than LDA and does not offer an alternative to LDA [38].…”
Section: Chemometrics For Olive Oil Classification According To Its Qmentioning
confidence: 99%
“…In SIMCA, it is important to select the optimal number of PC for each class (fresh and expired class). The optimal number of PCs can be chosen based on explained variance or determined by (double) crossvalidation [23]. In recent work, Basri et al utilized two parameters namely predicted residual error sum of squares (PRESS) and explained variance to select optimal number of PCs [24].…”
Section: Development Of Simca Classification Modelmentioning
confidence: 99%
“…This is because the method groups objects together based on applying a PCA to each class of the training set. The ideal number of PCs can be determined by either double cross-validation or amount of explained variance or in some cases, it may be predetermined (Rácz et al,2018). Although SIMCA is a class-modelling technique, it is commonly used as a discriminatory tool in chemometrics.…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…Although SIMCA is a class-modelling technique, it is commonly used as a discriminatory tool in chemometrics. This is warned against by a meta-analysis conducted by Rácz et al (2018), which shows that SIMCA was repeatedly outperformed for the task of discrimination by 29 different methods which includes the majority of the major categories of the available classification methods, such as linear and quadratic discriminant analysis (LDA), Classification and Regression Tree analysis (CART), PLS-DA, k-NN, to name a few.…”
Section: Qualitative Methodsmentioning
confidence: 99%